Socio-economic profile of pure - bred dog owners in Puducherry (Indian Journal of Animal Production and Management, 2017)
A study was carried out to assess the socio-economic profile of pure - bred dog owners in Puducherry  region of the Union Territory of Puducherry. 150 dog owners were selected as respondents who owned  164 dogs of different breeds.The mean age of the dog owners was 40.04 years. Male members of the  household were reported to be the owners of the dog in the majority of the households. Majority of them  were graduates and working in private sector. Their experience in dog rearing was 7.26 years on an average,  and the average number of dogs owned per household was 1.09 dogs. The average age of the dog was  37.55 months at the time of the study, and male dogs were more than female dogs.
Keywords: Companionship; Dog license; Guarding; Pure-bred dogs